Insights into the paradoxical effect of smoking on vasculitis: a comprehensive review - Khabbazi, Alireza; Rahimi, Mehran; Malek Mahdavi, Aida; Farzaneh, Rojin; Daneshvar, Sara; Naseri, Amirreza; Beig Zali, Saman; Nasiri, Ehsan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Vasculitis is a group of uncommon diseases characterized by inflammation of blood vessels, which contributes to the organ ischemia and damage. Cigarette smoke contains a high concentration of various toxins, which have the potential to affect the immune response and development of autoimmune/autoinflammatory rheumatic diseases including vasculitis. Smoking influences both innate and adaptive immune systems and plays binary functions in modulating immunity by either aggravating pathogenic immune responses or attenuating defensive immunity. Smoking contributes to the pathogenesis of autoimmune diseases by various mechanisms including induction of tissue damage and apoptosis, changes in innate immune function and production of proinflammatory cytokines, changes in humoral immunity and T cell responses and anti-estrogen effects. In this review, we considered the available evidence on the association between smoking with the risk, clinical manifestations, response to treatment and outcomes of vasculitis, and the effect of smoking cessation on these parameters. In conclusion, despite inconclusive evidence of an increased risk of giant cell arthritis and anti-neutrophil cytoplasmic autoantibody associated vasculitis (AAV) in smokers, there is strong evidence that smokers have a lower risk of Behcet’s disease (BD). Furthermore, smoking changes the clinical picture and outcomes of BD and AAV.